Development of Application-based Interactive Science E-Modules PocketBook to Improve the Digital Literacy and Creative Thinking of Middle School Students - Pratama, Fiky Ahmad Kanzul Fikri; Wahyuni, Sri; Putra, Pramudya Dwi Aristya (Jurnal Paedagogy, 2024)
This research aims to develop an application-based interactive Science E-Module PocketBook to improve the digital literacy and creative thinking of junior high school students. This research method used research and development with a 4D model (Define, Design, Develop, and Disseminate). Validation of the E-Module was carried out at the Jember University Master of Science Education campus while the validity test, practicality test, and effectiveness test of the application-based interactive Science E-Module PocketBook was carried out at SMPN 10 Jember and SMPN 12 Jember. The subjects in this development were class VIII even semester students. Results This research showed that the average validity score obtained is 86% by expert validators. The percentage of response results from the limited scale and class scale tests at SMPN 10 Jember were respectively 85.1% and 86.6%, each score can be categorized as very valid. Application-based interactive science e-module PocketBook It not only contains material but there are also assignments to improve students' digital literacy and creative thinking. Application-based interactive science e-module PocketBook the theme of vibrations and waves has also been distributed to two classes at SMPN 12 Jember with student response scores of 81.9% and 85.3% respectively.